Physical Condition Profile of Silat-Atletesselection Of Students Education and Exercise Center (PPLP), and Students Education and Training Center (PPLM) Dispora Riau Province in 2018 - Ramadi, Ramadi; Sulastio, Agus; Elva, Maryan (Proceedings of the UR International Conference on Educational Sciences, 2018)
The purpose of this study was to find out the physical condition profile of athletes selection of the Student Training and Education Center (PPLP) and Student Training and Education Center (PPLM) in the Province of Riau in 2018, and to find out the Difference in Physical Conditions of Silat Athlete Education and Training Centers Students (PPLP) and Student Training and Education Center (PPLM) in the Province of Riau in 2018. The type of this research was Quantitative Descriptive, where this study would clearly illustrate the physical condition data of PPLP and PPLM team selection of Riau Province. In this study, researchers used a physical condition test for the collecting data. Based on the results and discussion it can be concluded that the results of the physical condition data of candidates for Silat Putra PPLP athletes are in the medium category with a percentage of 75%, and the low category with a percentage of 25%. Whilst for the SilatPutri PPLP athlete, it is a medium category (1 person only) with a percentage of 25%, and there are 3 people with low category(with a percentage of 75%). Furthermore, for the PPLM Silat Putra athletes are as follows: the good is 2 people (50%), the medium category is 1 person (25%), and thelow category is 1 person (25%). Whilst, for the SilatPutri PPLM athletes, the medium category is 3 people (75%), the low category has 1 person (25%). Thus, the condition of PPLM athletes selection participants is better than PPLP. This is also influenced by the length of the athletes training.